Особливості функціонування банківської системи України в умовах глобалізації - Марич, М.Г. (Стратегія і механізми регулювання промислового розвитку, 2013)
Сформовано загальні аспекти та проблеми інтеграції вітчизняної банківської системи у світовий простір та розглянуто іноземний сегмент банків в Україні. Проаналізовано актуальну статистичну інформацію щодо кількості структурних підрозділів українських банків за кордоном та кількості іноземного капіталу у структурі банківської системи України. Сформированы общие аспекты и проблемы интеграции отечественной банковской системы в мировое пространство и рассмотрен иностранный сегмент банков в Украине. Проанализирована актуальная статистическая информация о количестве структурных подразделений украинских банков за рубежом и количестве иностранного капитала в структуре банковской системы Украины. The article identifies the general aspects and problems concerning the integration of the domestic banking system into the global space, and considers the foreign segment of commercial banks in Ukraine. The urgency of the study consists in the consideration of the process of economic internationalization, increase of volumes of the international money flows which are served by the commercial banks. Therefore, the aim of the study is to determine the state of the domestic banking system in the aspect of its global integration. The subject of the study is the banking system of Ukraine including its foreign segment. Using the annual reports, figures of the National Bank of Ukraine and scientific publications the author analyzes relevant statistical information about changesin the number of structural subdivisions (branches and representative offices) of the Ukrainian banks situated abroad as well as their geographical location during 2006-2013. The problems concerning the integration of the national segment in the global banking space are identified. The issues concerning the number of foreign banks in Ukraine were studied, as well as the problems concerning their outflow from the domestic banking system in the latest few years, and the dynamics of amounts of foreign capital in the structure of Ukraine’s banking system during the last seven years was analyzed. The study reveals a negative aspect of low rates of Ukraine’s banks expansion abroad, negative dynamics of the indicator reflecting the share of foreign capital in Ukraine’s banks as well as its simultaneous substitution by the domestic capital. Both positive and negative aspects of the given research results are analyzed, the proper conclusions are made, and the possible ways of further development of Ukraine’s banking system are described in the aspect of its integration in the global financial space.